Human parathyroid gland single nucleus RNAseq datasets - James Koh (22676969) (2025)
These datasets include snRNAseq output from a study examining human parathyroid tissue. The datasets include comparison tables delineating transcriptional signatures associated with specific cellular subsets and metabolic states of human parathyroid glands.